2014
DOI: 10.1521/aeap.2014.26.4.328
|View full text |Cite
|
Sign up to set email alerts
|

HIV Testing Among MSM in Bogotá, Colombia: The Role of Structural and Individual Characteristics

Abstract: This study used mixed methods to examine characteristics related to HIV testing among men who have sex with men (MSM) in Bogotá, Colombia. A sample of 890 MSM responded to a computerized quantitative survey. Follow-up qualitative data included 20 in-depth interviews with MSM and 12 key informant interviews. Hierarchical logistic set regression indicated that sequential sets of variables reflecting demographic characteristics, insurance coverage, risk appraisal, and social context each added to the explanation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 23 publications
5
41
1
1
Order By: Relevance
“…Having a history of STI was associated with the outcome, as has been observed in other studies (25,27,34). The presence of STI increases the risk of contracting HIV (26) and also increases self-perceived risk (25).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Having a history of STI was associated with the outcome, as has been observed in other studies (25,27,34). The presence of STI increases the risk of contracting HIV (26) and also increases self-perceived risk (25).…”
Section: Discussionsupporting
confidence: 73%
“…The presence of STI increases the risk of contracting HIV (26) and also increases self-perceived risk (25). In addition, symptoms of some STI prompt engagement with healthcare services and thereby increase the likelihood of the suggestion of a test by a healthcare provider.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Access to treatment is limited by barriers that include limited financial resources, lack of awareness of available services, and limited availability of endocrinologists (Triana Duarte, 2013). In addition, stigma is evident in medical settings and can result in inadequate care for transgender individuals and other sexual minorities (Poteat, German, & Kerrigan, 2013), including in Colombia (Reisen et al, 2014). Research has indicated that barriers to medical care lead some transgender persons to seek alternative ways of achieving feminization, such as self-administration of hormones and implants (Clements-Nolle, Marx, Guzman, & Katz, 2001; Garofalo, Deleon, Osmer, Doll, & Harper, 2006; Rotondi et al, 2013; Sanchez, Sanchez, & Danoff, 2009; Xavier, Honnold, & Bradford, 2007).…”
Section: Body Modificationmentioning
confidence: 99%